2022
DOI: 10.1021/acs.jnatprod.1c00960
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis-Inhibitory Piperidine Alkaloids from the Leaves of Microcos paniculata

Abstract: Eight new 2,6-disubstituted piperidin-3-ol alkaloids (1−8), featuring a C 10 unsaturated alkyl side chain, together with three previously reported analogues (9−11) were isolated from the leaves of medicinal plant Microcos paniculata. Their structures and absolute configurations were elucidated unambiguously by means of 1D and 2D NMR spectroscopic data analysis, modified Mosher's method, Snatzke's method, and quantum chemical electronic circular dichroism (ECD) calculations, as well as single-crystal X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Thus, all three would share the same absolute configuration of the three common stereogenic centers around the piperidine ring. 10 This assertion has very recently found credence in the results of the studies of Che, Ye, and Wang et al, 5 who reported the (re)isolation of microgrewiapine A (albeit from the leaves rather than the stem bark) of M. paniculata . They determined the structure and relative configuration of their sample of microgrewiapine A unambiguously by single-crystal X-ray diffraction analysis and assigned the (2 S ,3 R ,6 S ) absolute configuration to the alkaloid by comparison of its experimental ECD spectrum with the calculated ECD spectra [CAM-B3LYP/6-31+G(d)] of both enantiomers.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…Thus, all three would share the same absolute configuration of the three common stereogenic centers around the piperidine ring. 10 This assertion has very recently found credence in the results of the studies of Che, Ye, and Wang et al, 5 who reported the (re)isolation of microgrewiapine A (albeit from the leaves rather than the stem bark) of M. paniculata . They determined the structure and relative configuration of their sample of microgrewiapine A unambiguously by single-crystal X-ray diffraction analysis and assigned the (2 S ,3 R ,6 S ) absolute configuration to the alkaloid by comparison of its experimental ECD spectrum with the calculated ECD spectra [CAM-B3LYP/6-31+G(d)] of both enantiomers.…”
mentioning
confidence: 83%
“…They determined the structure and relative configuration of their sample of microgrewiapine A unambiguously by single-crystal X-ray diffraction analysis and assigned the (2 S ,3 R ,6 S ) absolute configuration to the alkaloid by comparison of its experimental ECD spectrum with the calculated ECD spectra [CAM-B3LYP/6-31+G(d)] of both enantiomers. 5 The specific rotation value of their sample of microgrewiapine A {[α] D 25 −22.8 ( c 8.5, MeOH)} 5 was, however, found to be opposite in sign to the value originally reported by Kinghorn et al {[α] D 25 +15.4 ( c 0.1, MeOH)} 1 for their sample of the alkaloid [note that although the concentrations of these samples are very different, their relative magnitudes are consistent with our previous observation of increasing magnitude of the specific rotation value of our synthetic sample of microgrewiapine A with increasing concentration of the sample {[α] D 25 −16.0 ( c 0.1, MeOH); [α] D 25 −24.6 ( c 0.5, MeOH); [α] D 25 −26.2 ( c 1.0, MeOH)}]. 9 As Kinghorn et al had also assigned the (2 S ,3 R ,6 S ) absolute configuration to their sample of microgrewiapine A on the basis of the results of a Mosher’s ester analysis, 1 it now seems almost certain that a typographical error of sign of the specific rotation value was made by Kinghorn et al in the report of the original isolation study, 1 as this is the only outlier from the significant weight of evidence now consistent with natural microgrewiapine A possessing the (2 S ,3 R ,6 S ) absolute configuration; hence it seems that microcosamine A, microgrewiapine A, and microgrewiapine B are indeed “three homochiral alkaloids”.…”
mentioning
confidence: 99%
See 3 more Smart Citations